Modern MR Imaging Technology in Rectal Cancer; There Is More Than Meets the Eye - Haak, Hester E.; Maas, Monique; Trebeschi, Stefano; Beets-Tan, Regina G. H. (Frontiers in Oncology, 2020)
MRI is now part of the standard work up of patients with rectal cancer. Restaging MRI has been traditionally used to plan the surgical approach. Its role has recently increased and been adopted as a valuable tool to assist the clinical selection of clinical (near) complete responders for organ preserving treatment. Recently several studies have addressed new imaging biomarkers that combined with morphological provides a comprehensive picture of the tumor. Diffusion weighted MRI (DWI-MRI) has entered the clinics and proven useful for response assessment after chemoradiotherapy. Other functional (quantitative) MR-imaging technologies are on the horizon including artificial intelligence modeling. This narrative review provides an overview of recent advances in rectal cancer (re)staging by imaging with a specific focus on response prediction and evaluation of neoadjuvant treatment response. Furthermore, directions are given for future research.